Early Cretaceous basalts record the modification of the North China Craton lithospheric mantle: implications for lithospheric thinning. Issue 9 (15th May 2022) - Chang, Zeguang; Dong, Guochen; Scott, James M.
ABSTRACT: The modification of the Archaean lithospheric mantle root beneath the eastern North China Craton (NCC) has been noticed. However, the degree of modification and the characteristics of metasomatic agents for the NCC lithospheric mantle are still unclear. Here, we compile the geochemistry and 87 Sr/ 86 Sr and 143 Nd/ 144 Nd isotope ratios of Cretaceous primitive basalts (Yixian, Sihetun, Fangcheng and Feixian) from the eastern NCC and estimate the inputs of subduction-related elements into the Archaean lithospheric mantle beneath the NCC. These basalts show primitive (high MgO, Cr and Ni contents) and arc-like geochemical features (enrichments in LILEs and depletions in HFSEs) that indicate that the mantle sources were modified by fluids related to subducted crustal materials. Substantial proportions of subduction-mobile elements (e.g. ~95% Ba and ~90% Th) transferred to the basalt sources via hydrous melts. Thus, a large volume of fluids transferred into the lithospheric mantle. The data support the model that the NCC Archaean lithospheric mantle was weakened by hydrous melts, which resulted in a fusible weakened lithospheric mantle. Preliminary lithospheric thinning was induced by the extension of the NCC resulting from trench retreat of the Paleo-Pacific plate at ~140-120 Ma. Then, decompression melting of the lithospheric mantle caused pervasive melts in the weakened lithospheric mantle, resulting in the lithospheric mantle having a low viscosity comparable to the asthenospheric mantle, which principally reduced the lithospheric mantle.